Analisis Pengelolaan Linen di Instalasi Laundry - Retika, Nelya; Samino, Samino; Amirus, Khoidar (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2021)
Analysis of Linen Management in The Laundry Installation of The Pringsewu General Hospital Background: Laundry installation is one of the non-medical supports that have an important role as the person in charge in providing linen services to hospital patients, especially inpatients. An increase of 0.5% of hospitalized patients were found to have new infections. 15 kg of dirty linen produced every day is still mixed with infectious and non-infectious linen, inadequate linen management human resources (HR), linen management officers do not use complete Personal Protective Equipment (PPE) when doing work, linen transportation does not use special trolley, clean linen does not meet the quantity and quality. Purpose: To analyze linen management in the Laundry Installation of Pringsewu Hospital. Methods: Qualitative research with descriptive analysis. Purposive sampling informant retrieval technique. There are 4 informants including 1 key informant and 3 main informants. Data collection techniques are observation, in-depth interviews, literature studies, and document review. Results: The education level of linen managers is from elementary to junior high school and has not received special training, the number of employees is 3 people, funds are insufficient so that the facilities are still incomplete, and the application of standard operating procedures (SOP) is not optimal. Conclusion: The management of linen in the laundry installation has not run optimally. This can be seen from human resources, completeness of facilities, funds, and application of SOP. Keywords: Linen management; Patients; Laundry installation Pendahuluan: Instalasi laundry merupakan salah satu penunujang non medik yang memiliki peran penting sebagai penanggungjawab pada penyediaan layanan linen terhadap pasien rumah sakit, terutama pasien rawat inap. Ditemukan 0.5% kenaikan pasien rawat inap mendapat infeksi baru. Linen kotor yang dihasilkan per hari 15 kg masih tercampur linen infeksius dan non infeksius, sumber daya manusia (SDM) pengelola linen belum memadai, petugas pengelola linen tidak menggunakan alat pelindung diri (APD) lengkap saat melakukan pekerjaan, pengangkutan linen tidak menggunakan troli khusus, linen bersih belum memenuhi kuantitas dan kualitas. Tujuan: Untuk menganalisis pengelolaan linen di Instalasi Laundry RSUD Pringsewu. Metode: Penelitian kualitatif dengan analisis deskriptif. Teknik pengambilan informan purposive sampling. Terdapat 4 informan meliputi 1 informan kunci dan 3 informan utama. Teknik pengumpulan data observasi, wawancara mendalam, studi literatur, dan telaah dokumen. Hasil: Tingkat pendidikan SDM pengelola linen yaitu SD sampai SMP dan tidak mendapat pelatihan khusus, jumlah tenaga sebanyak 3 orang, dana belum mencukupi sehingga sarana masih belum lengkap, dan pelaksanaan standar operasional prosedur (SOP) belum optimal. Simpulan: Pengelolaan linen di instalasi laundry berjalan belum optimal. Dapat dilihat dari SDM, kelengkapan sarana, dana, dan pelakasanaan SOP.